Luther's Outlaw God : Volume 3: Sacraments and God's Attack on the Promise - Paulson, Steven D. (Book collections on Project MUSE., 2021)
In this third of three volumes addressing Luther's outlaw God, Steven D. Paulson invites readers to embark on the deepest, hardest, most glorious of all God's ways of hiding: God hiding a third time in the preached word or sacraments. Paulson's grasp of historical, theological, and hermeneutical scholarship is on full display in this volume, but always in service of proclamation of the gospel. Readers and proclaimers: prepare to be provoked, enlightened, and inspired.